The heart of winter : a novel [large type] - Evison, Jonathan (Thorndike Press large print dynamic drama., 2025)
"Abe Winter and Ruth Warneke were never meant to be together--at least if you ask Ruth. Yet their catastrophic blind date in college evolved into a seventy-year marriage and a life on a farm on Bainbridge Island with their hens and beloved Labrador Megs. Through the years, the Winters have fallen in and out of lockstep, and out of their haunting losses and guarded secrets, a dependable partnership has been forged. But when Ruth's loose tooth turns out to be something much more malicious, the beautiful, reliable life they've created together comes to a crisis"--